Bacillus velezensis FZB42 in 2018: The Gram-Positive Model Strain for Plant Growth Promotion and Biocontrol - Fan, Ben; Wang, Cong; Song, Xiaofeng; Ding, Xiaolei; Wu, Liming; Wu, Huijun; Gao, Xuewen; Borriss, Rainer (Frontiers in Microbiology, 2018)
Bacillus velezensis FZB42, the model strain for Gram-positive plant-growth-promoting and biocontrol rhizobacteria, has been isolated in 1998 and sequenced in 2007. In order to celebrate these anniversaries, we summarize here the recent knowledge about FZB42. In last 20 years, more than 140 articles devoted to FZB42 have been published. At first, research was mainly focused on antimicrobial compounds, apparently responsible for biocontrol effects against plant pathogens, recent research is increasingly directed to expression of genes involved in bacteria-plant interaction, regulatory small RNAs (sRNAs), and on modification of enzymes involved in synthesis of antimicrobial compounds by processes such as acetylation and malonylation. Till now, 13 gene clusters involved in non-ribosomal and ribosomal synthesis of secondary metabolites with putative antimicrobial action have been identified within the genome of FZB42. These gene clusters cover around 10% of the whole genome. Antimicrobial compounds suppress not only growth of plant pathogenic bacteria and fungi, but could also stimulate induced systemic resistance (ISR) in plants. It has been found that besides secondary metabolites also volatile organic compounds are involved in the biocontrol effect exerted by FZB42 under biotic (plant pathogens) and abiotic stress conditions. In order to facilitate easy access to the genomic data, we have established an integrating data bank ´AmyloWiki´ containing accumulated information about the genes present in FZB42, available mutant strains, and other aspects of FZB42 research, which is structured similar as the famous SubtiWiki data bank.